The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1017/s0003356100002841
|View full text |Cite
|
Sign up to set email alerts
|

Mammogenesis and first lactation milk yields of identical-twin heifers following pre-pubertal administration of bovine growth hormone

Abstract: The effects of long-term administration of bovine growth hormone (GH) on pre-pubertal mammogenesis and subsequent milk production were examined in pasture-fed dairy heifers. Purified bovine GH (specific activity 0·78 i.u. per mg) was administered daily for 21 weeks (0·6 mg GH per kg M 0·75) to one member of each of 12 sets of twins from 3·5 (range 2·5 to 4-5) months of age. GH administration resulted in a significantly smaller mammary gland compared with control heifers at slaughter at the end of treatment (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
1
4

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
7
12
1
4
Order By: Relevance
“…Specifically, GH acts on mammary stromal and epithelial tissues in rats to induce the differentiation of ductal epithelia into terminal end buds (TEBs) and alveolar structures and promotes the morphogenesis of the TEBs in the mammary fat pad (Walden et al 1998). GH administration to peri-pubertal heifers (Sejrsen et al 1986, Sandles et al 1987, Purup et al 1993) and lambs (McFadden et al 1990) similarly increases the amount of parenchymal tissue, although overall mammary size may not be increased, and immunization of heifers against GHRH similarly impairs pubertal mammary development (Sejrsen et al 1999). Increased milk yield resulting from peripubertal GH administration has not, however, been observed in numerous studies in heifers (reviewed by Sejrsen et al 1999).…”
Section: Mammogenesismentioning
confidence: 99%
“…Specifically, GH acts on mammary stromal and epithelial tissues in rats to induce the differentiation of ductal epithelia into terminal end buds (TEBs) and alveolar structures and promotes the morphogenesis of the TEBs in the mammary fat pad (Walden et al 1998). GH administration to peri-pubertal heifers (Sejrsen et al 1986, Sandles et al 1987, Purup et al 1993) and lambs (McFadden et al 1990) similarly increases the amount of parenchymal tissue, although overall mammary size may not be increased, and immunization of heifers against GHRH similarly impairs pubertal mammary development (Sejrsen et al 1999). Increased milk yield resulting from peripubertal GH administration has not, however, been observed in numerous studies in heifers (reviewed by Sejrsen et al 1999).…”
Section: Mammogenesismentioning
confidence: 99%
“…This decrease was brought about by a diminished feed intake which was significant during the 4th wk of lactation in LACT and GEST-LACT sows (Farmer et al 1992). A decrease in extraparenchymal tissue was also reported in GH-treated (Sandles et al 1987;Purup et al 1993) and in GRF-injected prepubertal heifers (Ringuet et al 1989) and was said to be due to the lypolytic action of GH. For personal use only.…”
Section: Farmer Et Al -Grf and Mammary Gland Development 337mentioning
confidence: 84%
“…Hence, milk production is a function of alveolar cell number and of the metabolic activity of these cells along with the metabolic support provided by other body tissues. Previously published results have reported either no change (Purup et al 1993) or an increase (Sandles et al 1987;Ringuet et al 1989) in mammary parenchyma of peripubertal heifers receiving GH or GRF. Increases in parenchymal protein (Purup et al 1993) and in total parenchymal DNA (Sandles et al 1987) have also been observed in GH-treated heifers.…”
Section: Farmer Et Al -Grf and Mammary Gland Development 337mentioning
confidence: 85%
See 2 more Smart Citations